REFERENCE TO THE ADAGE "WHAT IS GOOD FOR THE GOOSE IS ALSO GOOD FOR THE GANDER” IN RELATION TO THE GOLDEN RULE AS BASIS FOR THE UNITY OF NIGERIA - Nwanguma, Chibuzo I; Nzeh, Atracta A; Oti, Rotimi A (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2025)
This study addresses the unhealthy unity in Nigeria, which, since its inception, has been fraught with gross unrest, chasm, and rancour amid the ethnic groups within the system. This anomaly occasioned the regrettable ‘Wild Wide West’ that incidentally ushered in the upheaval that indeed caused the ethnic cleansing and civil war of the 1960s. Kids who were taught of national unity in colleges or read of it in their textbooks while in school tend to get extremely exasperated as they see and experience outright different thing amid the society in their career endeavors within the country. This unprecedented departure from true unity has caused untold insidious fracas in the country recently, and addressing it in the academia is just an urgent necessity. In carrying out this study from a cultural perspective, the Igbo adage analytically explained in the article is used vis-à-vis the popular maxim by Jesus in the Gospels, especially from the Matthean account otherwise christened the “Golden Rule.” The approaches considered effective for elucidation of facts therewith are an exegesis of the selected passage and contextual analysis of the theme. Liberation theology was used to address this issue in the context of the present study. The study concluded that restructuring is non-negotiable if Nigeria must remain a nation, and the same is one of the recommendations of the work.